Determinação de trechos críticos da Rodovia Marechal Rondon no perímetro urbano da cidade de Bauru - Lipi, Bruno Kanabara (Universidade Federal de São Carlos, 2022)
Traffic accidents happen at a high frequency around the world. Every year, millions of these incidents end up having severe consequences, including social, environmental and material loss. This reality is even worse in undeveloped or emerging countries, such as Brazil. The high level of traffic accidents occur due to the lack of financial sources, which are guaranteed for immediate investment measures, like health and public security. Thus, roads and streets tend to suffer negative impacts over its project execution, as well as the further conservation, given the low financial fund. Furthermore, the lack of traffic safety consciousness increases the chances of having these accidents happening more often, once they value mobility instead. This issue is very likely to happen along highways that cover the urban perimeter, becoming a barrier to the pedestrians, besides having the highway traffic interfere with the city’s traffic. Having mentioned that, some program aims to reduce the traffic accidents’ impacts through prevention or mitigating actions. It is extremely important to study the roads system and the sources of the accident through critical points identification. Consequently, this work shows the identification of critical points in Marechal Rondon Highway, over its urban perimeter in Bauru and São Paulo, through data analysis from former registers. It has been observed that highway sections that are closer to the urban perimeter with access to the city, show a large number of accidents and a high level of severity than sections that are more distant from the urban concentration. Moreover, the difference between distinct ways to measure standards to obtain the results of high or low critical sections is notable, leading to the conclusion that the best methodology depends on the goal to be achieved
Determination of critical stretches of the Marechal Rondon Highway in the urban perimeter of Bauru city
Keywords: Acidente de trânsito; Rodovias; Perímetro urbano; Trecho crítico; Análise de dados; Ações mitigadoras; Índice de severidade; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::OPERACOES DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES